Bioactive Azadirachta indica and Melia azedarach leaves extracts with anti-SARS-CoV-2 and antibacterial activities - Hemdan, Bahaa A.; Mostafa, Ahmed; Elbatanony, Marwa M.; El-Feky, Amal M.; Paunova-Krasteva, Tsvetelina; Stoitsova, Stoyanka; El-Liethy, Mohamed Azab; El-Taweel, Gamila E.; Abu Mraheil, Mobarak; Justus Liebig University Giessen (My University, 2023)
The leaves of Azadirachta indica L. and Melia azedarach L., belonging to Meliaceae family, have been shown to have medicinal benefits and are extensively employed in traditional folk medicine. Herein, HPLC analysis of the ethyl acetate fraction of the total methanolic extract emphasized the enrichment of both A. indica L., and M. azedarach L. leaves extracts with phenolic and flavonoids composites, respectively. Besides, 4 limonoids and 2 flavonoids were isolated using column chromatography. By assessing the in vitro antiviral activities of both total leaves extracts against Severe Acute Respiratory Syndrome Corona virus 2 (SARS-CoV-2), it was found that A. indica L. and M. azedarach L. have robust anti-SARSCoV- 2 activities at low half-maximal inhibitory concentrations (IC50) of 8.451 and 6.922 μg/ mL, respectively. Due to the high safety of A. indica L. and M. azedarach L. extracts with half-maximal cytotoxic concentrations (CC50) of 446.2 and 351.4 μg/ml, respectively, both displayed extraordinary selectivity indices (SI>50). A. indica L. and M. azedarach L. leaves extracts could induce antibacterial activities against both Gram-negative and positive bacterial strains. The minimal inhibitory concentrations of A. indica L. and M. azedarach L. leaves extracts varied from 25 to 100 mg/mL within 30 min contact time towards the tested bacteria. Our findings confirm the broad-spectrum medicinal value of A. indica L. and M. azedarach L. leaves extracts. Finally, additional in vivo investigations are highly recommended to confirm the anti-COVID-19 and antimicrobial activities of both plant extracts.
Keywords: ddc:610